Initiating Climate Adaptation in a Western Larch Forest - Justin S Crotteau; Elaine Kennedy Sutherland; Theresa B Jain; David K Wright; Melissa M Jenkins; Christopher R Keyes; Linda M Nagel (Forest Science, 2019)

Management and Succession at the Lick Creek Demonstration/Research Forest, Montana - Justin S Crotteau; Sharon M Hood; Duncan C Lutes; Christopher R Keyes; Anna Sala; Michael G Harrington (Journal of Forestry, 2018)

Application of mathematical models in the spatial analysis of early tree seedling distribution patterns within a treefall gap at Gwangneung Experimental Forest, Korea - Woongsoon Jang; Christopher R. Keyes; Jong-Hwan Lim (Journal of Plant Biology, 2013)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Seed rain of ponderosa pine beneath partial overstories - Christopher R. Keyes; Douglas A. Maguire (New Forests, 2007)

Observed dynamics of ponderosa pine (Pinus ponderosa var. ponderosa Dougl. ex Laws.) seedling recruitment in the Cascade Range, USA - Christopher R. Keyes; Douglas A. Maguire; John C. Tappeiner (New Forests, 2007)